Salman Al-Farisi Sebagai Model Inovator Unggul - Wan Abdullah, W. A. A.; Mohd Zhaffar, N.; Abdul Razak, K.; Hamzah, M. I. (Universiti Sains Islam Malaysia, 2024)
The technology-driven world nowadays demands that all people strive to be innovators. This is why education systems need to be constantly changed to prepare students to be future innovators. Therefore, the nature of an ideal innovator needs to be taken into account in order to serve as an appropriate example for the students as the future innovators. This study focuses on Salman al-Farisi as a model innovator. It was performed qualitatively using a form of content analysis on Salman's trait. The findings show that there are 11 innovative traits in Salman, namely; knowledgeable, crazy and brilliant ideas, high curiosity, self-reliant, always looking for the best, sticking to the truth, evaluating things meticulously, having clear goals, always careful, funny and modest. These findings form the Salman's Innovator Model.